REGION AND NATION: THE INSURGENT RIO GRANDE BETWEEN THE BRAZILIAN EMPIRE AND THE RIVER PLATE’S REPUBLICS (1838-1842) - Bossak de Figuereido, Joana; Barcellos Guazzelli, César A. (Revista de Historia Social y de las Mentalidades, 2024)
The ninteenth century was marked by the  decolonization process and the consequent  national state formation process in Latin- America. During many years the civil wars  between the different political groups were  the most visible characteristic of those times.  The present article seeks an explanation to  the secession of the Brazilian province of  Rio Grande do Sul, located in the extreme  south of the country, in the frontier with the  Oriental State of Uruguay and the Argentine  Confederation. The insurgents proclaimed  their independence from the Empire of Brazil  under the name of Riograndense Republic,  managing to establish right away political and  economical commitments with the neighboring  republics as a way of securing itself against the  Brazilian government’s efforts to reintegrate his  former province. The Riograndense Republic  maintained itself from 1836 to 1845, yet the text  shows the most important diplomatic acts of the  rebels, which occurred between 1838 and 1842.
Keywords: National State; Provinces; Frontiers; Civil Wars; Warlords